2000
DOI: 10.1093/jat/24.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Testosterone/Epitestosterone Ratio Influential Factors as Determined in Doping Analysis

Abstract: The ratio of the concentration of testosterone glucuronide to the concentration of epitestosterone glucuronide (T/E ratio) as determined in urine is the most frequently used method to prove testosterone abuse by athletes. A T/E ratio higher than 6 has been considered as proof of abuse in the past; however, cases of naturally occurring higher T/E ratios have been described. Since the introduction of the T/E ratio in doping analysis, the parameters that may or may not influence the T/E ratio, possibly leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 92 publications
1
37
0
9
Order By: Relevance
“…The T/ET ratio is widely used as an antidoping control measure, but it has found relatively few applications in the clinical setting. Furthermore, very little scientific information is available regarding the excretion of T and ET during hypogonadism [49]. In one study by Hubl et al [50], it was shown that patients with hypogonadism excreted submolar amounts of both T and ET.…”
Section: Considerations On the Measurement Of The T/et Ratio In Patiementioning
confidence: 99%
“…The T/ET ratio is widely used as an antidoping control measure, but it has found relatively few applications in the clinical setting. Furthermore, very little scientific information is available regarding the excretion of T and ET during hypogonadism [49]. In one study by Hubl et al [50], it was shown that patients with hypogonadism excreted submolar amounts of both T and ET.…”
Section: Considerations On the Measurement Of The T/et Ratio In Patiementioning
confidence: 99%
“…E is of great interest in the field of human doping control because it is the denominator in the T/E ratio, an indirect marker of T administration. When T is administered to man, the excretion rate of urinary T increases, the excretion rate of E decreases and the T/E ratio increases (Van der Kerkhof et al, 2000). An increased T/E ratio is also an indirect marker of androstenedione and dehydroepiandrosterone administration.…”
Section: Introductionmentioning
confidence: 99%
“…No caso da testosterona, o limite tem por base a relação de concentração de testosterona/epitestosterona (T/ E) na urina. Um valor de T/E maior que 6 sugere o uso de testosterona pelo atleta (Van de Kerkhof et al, 2000). Desta forma, para essas substâncias, foi necessário fazer análise quantitativa.…”
Section: Tabela IV -Resultados Das Análises Por Gc-ms De Amostras De unclassified
“…No início da década de 80, a cromatografia gasosa acoplada à espectrometria de massas (CG-EM) surge como a técnica analítica de escolha para a detecção e quantificação de EAA em programas de controle da dopagem no esporte. Também, em 1983, foi estabelecida a razão Testosterona/Epitestosterona urinária maior que 6 (T/E > 6) para a constatação do uso de ésteres de testosterona por atletas e esportistas (Van de Kerkhof et al, 2000).…”
Section: Esteróides Androgênicos Anabólicos (Eaa) São Substâncias Natunclassified